EFEKTIFITAS PERIKSA PAYUDARA SENDIRI (SADARI) DALAM UPAYA PENANGANAN DINI KANKER PAYUDARA DI RSUD DR. DJOELHAM BINJAI TAHUN 2019 - Juliani Bangun; Elisabeth Dame Manalu; Selamat Ginting (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2020)
The number of new cases and deaths from cancer throughout the world based on data from the World Health Organization (WHO) in 2015 showed a significant increase. From 2008 to estimated in 2030 there were 17 million deaths and 26 million in the category of morbidity. The data is a warning to all countries, especially Indonesia. This study aims to determine Breast Self-Examination Effectiveness (BSE) in Early Breast Cancer Treatment Efforts in Dr. Hospital Djoelham Binjai in 2019. The type of research used is an analytical observation survey with a Cross Sectional design which aims to explain the relationship between independent variables (risk factors) and dependent variables. The results of this study are known that the most effective variable on breast self examination in the effort of early detection of breast cancer is family support, because it has an Exp Beta or Odds Ratio value of 57.5 which means that family support is very effective 57.5 times compared to respondents who lack of family support in the effort of early detection of breast cancer in Dr. RSUD Djoelham Binjai. The form of family support carried out by the respondent's husband was in the form of motivation, helping respondents to deliver to the hospital, as well as emotional support. Emotional support can give respondents feel comfortable, feel loved when experiencing depression, help in the form of enthusiasm, empathy, trust, attention so that respondents who receive it feel valuable in the family. Thus the respondent will try to find knowledge and be more positive in terms of breast self-examination correctly and effectively. It is expected that the family will always support BSE so that the respondent checks her own breasts, and the respondent is always aware of her breast health by increasing her behavior to examine her own breasts